2008
DOI: 10.1021/jm701561e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Screening of Mono- and Di-Aryl Technetium and Rhenium Metallocarboranes. A New Class of Probes for the Estrogen Receptor

Abstract: A series of mono and diaryl rhenium(I)-carborane derivatives were prepared using microwave heating and screened for their affinity for two isoforms of the estrogen receptor (ER). The rhenacarborane derivative [(RR'C 2B9H9)Re(CO)3](-) (R = p-PhOH, R' = H), which was generated by taking advantage of a recently discovered cage isomerization process, and the neutral nitrosated analogue [(RR'C2B9H9)Re(CO)2(NO)] (R = p-PhOH, R' = H) showed the highest affinities of the compounds screened. As a result, the (99m)Tc an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…6. The characteristic peaks of boron atoms of carborane bisphenol resol phenolic resins are well consistent with their precursory carborane bisphenol [31] . …”
Section: Characterization Of P1 and P2supporting
confidence: 63%
“…6. The characteristic peaks of boron atoms of carborane bisphenol resol phenolic resins are well consistent with their precursory carborane bisphenol [31] . …”
Section: Characterization Of P1 and P2supporting
confidence: 63%
“…[6] While these characteristics of how different estrogens bind to the ERs have been known for several years, [5, 7] there have been only sporadic attempts to exploit this unfilled space and flexibility of the ER binding pocket as an approach to enhance ligand binding affinity, SERM behavior, or ER subtype selectivity. Nevertheless, a number of ER ligands having diverse three-dimensional chemical scaffolds have emerged: representative examples are based on ferrocene, [8] carboranes, [1a, 9] bridged polycyclics, [10] and some other cyclopentadienyl metal tricarbonyl complexes (Figure 1). [11] We have contributed to this area as well.…”
Section: Introductionmentioning
confidence: 99%
“…This development started in the early 2000s with 18 F or 11 C containing compounds, 1 but studies published in the last few years also showed the advantage of microfluidics over conventional methods for metal containing radiopharmaceuticals. [2][3][4][5][6][7] The reason for the success of microfluidics is that downsizing reaction vessels to the micro-scale allows for better mixing of reactants, more efficient energy transfer, less radiolysis, faster reaction optimization, and overall improved reaction control. [1][2][3][4][5][6][7][8] However, limited throughput of microfluidic devices and the difficult interface between batch and continuous-flow processes used for different radiopharmaceutical preparation steps still hinder the routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The reason for the success of microfluidics is that downsizing reaction vessels to the micro-scale allows for better mixing of reactants, more efficient energy transfer, less radiolysis, faster reaction optimization, and overall improved reaction control. [1][2][3][4][5][6][7][8] However, limited throughput of microfluidic devices and the difficult interface between batch and continuous-flow processes used for different radiopharmaceutical preparation steps still hinder the routine clinical use. 9 Up to now, the clear advantage of microfluidic systems lies in the possibility of rapid reaction optimization with very low precursor consumption as shown by Mate et al 3 The remaining challenge of translating those optimization results to conventional (clinical) reaction vessels, but also to various microfluidic reactor designs without adding extensive additional experiments, could be addressed by determining kinetic constants and diffusion coefficients of the studied systems and calculating expected reaction times for the clinical applied reaction vessels.…”
Section: Introductionmentioning
confidence: 99%